FACTORS AFFECTING UTILIZATION OF ANTENATAL CARE: THE OPINION OF PREGNANT WOMEN - Azeem, Muhammad Abdul; Sohag, Aijaz; Memon, Samina; Bhatti, Munir (Pakistan Journal of Physiology, 2013)
Background: Antenatal care is one of the four pillar initiatives of the Safe Motherhood. This study was carried out to identify the factors affecting the utilization of antenatal care by expectant women of child bearing age and women’s opinion regarding antenatal care. Methods: A cross-sectional questionnaire based survey was conducted from October 2009 to April 2010 at Civil Hospital, Karachi where 250 pregnant women were included who registered for antenatal care after 14 weeks of gestation. Miscarriages during the study were excluded. The subjects were further classified on basis of residential, education status, and number of visits they paid for antenatal care. Results: There were 250 subjects who used preterm delivery antenatal care, and those who followed excess, standard and fewer visits were 125 (60%), 62 (29%), and 63 (30%) respectively. Multipara, urban residents, and well-educated women showed high number of standard visits. Women who were already diagnosed to have antenatal problems (46%) paid standard visits and previous negative birth experience (50%) paid excess visits. The parity levels were significantly correlated with level of education (r=0.5−0.8) and residential status (r=0.6−0.8). Conclusion: The inadequate use of antenatal care is associated with high parity, low education and poor socioeconomic conditions. Public awareness programme for better antenatal standards is suggested.